Manajemen Humas pada “Festival Seni dan Kreasi Anak” dalam Membangun Citra Merek Lembaga Pendidikan - Isna Faridatun Nadziroh; Mambaul Ngadhimah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
The increasing number of quality educational institutions has created new, fairly tight competition in managing educational institutions. To survive during competition, it is necessary to manage differentiating programs carried out by educational institutions to build a positive impression and image of the institution in the public mind. Children's arts and creative festival events integrated with public relations management are the right solution so that the programs run can be known to the general public with the advantages and uniqueness that are highlighted. This research is a case study research with a qualitative approach. Data collection techniques used include observation, interviews and documentation which are processed using interactive data analysis techniques Miles, Huberman, and Saldana models consist of four stages in the form of data collection, data condensation, data presentation, and data verification. The location of the research was conducted at SD Immersion with branding school-based multiple intelligences. This study aims to analyze how the process of implementing public relations management is carried out in line with the theory of Cultip, Center, and Brown which consists of collecting facts, defining problems, planning, implementing communication, and evaluating as steps in managing programs effectively and efficiently. The role of public relations management in children's arts and creativity festival with various competitions, used by SD Immersion as a step to build brand institutions to the general public through the dissemination of information related to student achievement, the use of learning models and methods, and the culture built by the institution.